Turning Trash into Treasure is Hard Work! How The Activities of Consumers and Reuse Enablers Extend Product Lifetimes - Nilsson, Karin; Becker Frahm, Lea; Rexfelt, Oskar; Strömberg, Helena; Nhu Laursen, Linda (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This paper explores the process of transferring second-hand products from one home to another. It focuses on three key participants: the consumer who is divesting products from their home, the consumer who purchases pre-owned items, and the second-hand and reuse enablers that facilitate this circulation of products. Current literature tends to concentrate solely on one of these groups—either consumers divesting products, second-hand and reuse enablers, or consumers buying pre-used items. This fragmented approach leaves gaps in understanding the complete process of product circulation. To address this knowledge gap, our study examines the entire process, starting from the moment a consumer decides to part with a product until that product finds a new owner. We conducted interviews with 20 consumers who are divesting products, 11 second-hand and reuse enablers, and 20 consumers who purchase pre-owned items. Our research identified three main product circulation processes and eight sub-processes: Donation, Commission Sale, and Sell-It-Yourself. Each circulation process involves a long series of activities carried out by the consumer divesting the product, the reuse enabler, or the consumer buying the item. By comparing these processes, we highlight that successful circular product exchanges require significant effort from all participants. Additionally, we demonstrate how the responsibility for these activities shifts depending on the chosen process, revealing the challenges associated with circular product transactions and how reuse enablers can support recirculation. This research contributes to a deeper understanding of the circular economy and its current struggles and opens discussions on how to overcome these challenges.